Transition and verification of ground fault protection method in Hokuriku Shinkansen line. Issue 1 (1st January 2016) - Koyanagi, Michiteru; Takino, Toshiaki; Hayashiya, Hitoshi; Matsuoka, Shigeyasu; Kumada, Akiko; Hidaka, Kunihiko
Abstract: The electrical discharge gaps called S type horn are applied to the ground fault detection and protection in AC traction power supply system for high speed railway called Shinkansen. In this method, the earth resistance of the steel pipe pillar is an important factor for the ground fault protection by the electrical discharge. In this study, the analyses of the transient characteristics of grounding fault are carried out by using EMTP, and the ground resistance value required to trigger discharge at S type horn was calculated. Moreover, the protection effect of a discharge gap called GP the substation equipment that is a discharge gap which is inserted between rails and substation mesh is evaluated.